Sob as contas do rosário: objetos e lugares da Festa em Louvor a Nossa Senhora do Rosário em Catalão, Goiás - Janaina Faleiro Lucas Mesquita (2016)
Festivity in Honor of Our Lady of the Rosary happens in the city of Catalão (GO-Brazil) for over 130 years which each year brings together a larger number of devotees, dancers and tourists. The Festivity involves celebrations and different social actors and each one has a specific role. Among them are ternos or guards, sets of dancers who walk the city streets praising Our Lady of the Rosary, St. Benedict, Santa Efigênia and other Saints who they are devoted to. They use in their performances some objects, such as boxes, tambourines or adufos, a kind of craft tambourine, bats and manguaras. The manufacture of these objects involves traditional knowledge, part of the heritage that structure and keeps the cultural manifestation alive. They have paramount importance in ternos, it is through the rhythm of boxes and tambourines or adufos that the songs of praise are sung. The bats and manguaras are the objects that provide movement to the choreography danced by hundreds of people in signal of faith and devotion. This praise, the religious and the commercial parts of the Festivity happen on city streets. The commercial part is composed of the stalls, steel or wood structures covered with canvas and the street vendors that are located near Rosary Churchyard, prime area of the city. In this same place happens most religious celebrations: Masses, rosaries and novenas. The square is transformed into the stage of the Festivity, covered structures are set up to accommodate the participants and thus the cultural event transforms the city, occupying the streets and establishing relations between places and people. Thus, objects and places become an essential part of completing the intangible heritage which is the Festivity, object that this research explores. This study aimed, therefore, to understand the importance of these elements within the Festivity, based on an interdisciplinary methodology from conceptual foundations analysis of Architecture, Urbanism, Geography, Sociology, History and Anthropology, and the use of methodological tools applied in field work, such as interviews.